2021
DOI: 10.2147/ijgm.s316280
|View full text |Cite
|
Sign up to set email alerts
|

IQGAP3 May Serve as a Promising Biomarker in Clear Cell Renal Cell Carcinoma

Abstract: The study was designed to mine the expression and roles of IQGAP3 in clear cell renal cell carcinoma (ccRCC). Methods: Expression profiles and clinical information were obtained from the Cancer Genome Atlas (TCGA) to estimate IQGAP3 expression in ccRCC, its relationship with patients' clinicopathological variables and prognosis, and the potential biological mechanisms. Results: IQGAP3 was highly expressed in ccRCC and indicated advanced clinical outcome and poor prognosis. IQGAP3 affected the progression of cc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…We have previously shown that the expression of IQGAP3 is associated with tumor progression in gastric cancer [11]. IQGAP3 has been reported to be upregulated in hepatocellular [18], clear cell renal cell [29,30] carcinomas, high-grade serous ovarian [31] and lung [20] cancers, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…We have previously shown that the expression of IQGAP3 is associated with tumor progression in gastric cancer [11]. IQGAP3 has been reported to be upregulated in hepatocellular [18], clear cell renal cell [29,30] carcinomas, high-grade serous ovarian [31] and lung [20] cancers, respectively.…”
Section: Discussionmentioning
confidence: 98%
“…IQGAP3 is crucial for cell cycle, genome stability and tumor stem cell potential [ 27 ]. Growing evidence suggests that IQGAP3 is a biogenetic or prognostic marker of malignancy that promotes migration, invasion, and drug resistance in many human malignancies [ 28 ], such as gastric cancer [ 29 ], clear cell renal cell carcinoma [ 13 ], bladder cancer [ 30 ], and liver cancer [ 31 ]. This suggests that IQGAP3 may be an important oncogene.…”
Section: Discussionmentioning
confidence: 99%